Continuous Sorption of Remazol Brilliant Orange 3R Using Caulerpa scalpelliformis Biochar - Gokulan Ravindiran; Pradeepkumar Sugumar; Elias G (Advances in Materials Science and Engineering)
An ever increase in the utilization of water for domestic and industrial activities resulted in the depletion of fresh water. Water is being used in huge quantities for manufacturing and other activities. The toxic pollutants used in the industries get mixed with water and result in the degradation of water quality. Textile industries are considered as one of the major industries that release a huge quantity of wastewater. The dye used in the textile industries is not completely utilized in the dyeing process and gets mixed with water and reaches the environment. Caulerpa scalpelliformis, a novel sorbent, was used for the preparation of biochar and successive removal of dyes in a continuous operation. The operating conditions, namely, biochar bed depth, dye flow rate, and initial dye concentration, were investigated, and the experimental result was validated with the mathematical models.